Enhanced long-term strength and durability of shotcrete with high-strength C12A7 mineral-based accelerator. (October 2015) - Won, Jong-Pil; Hwang, Un-Jong; Lee, Su-Jin
Abstract: This study evaluated the performance of shotcrete using high strength C12 A7 mineral-based accelerator that has been developed to improve the durability and long-term strength. Rebound, compressive strength and flexural strength were tested in the field. Test result showed that existing C12 A7 mineral-based accelerator exhibits better early strength than the high-strength C12 A7 mineral-based accelerator until the early age, but high-strength C12 A7 mineral-based accelerator shows about 29% higher at the long-term age of 28 days. Microstructural analysis such as scanning electron microscope (SEM), X-ray diffraction (XRD) and nitrogen adsorption method was evaluated to analyze long-term strength development mechanism of high strength C12 A7 mineral-based accelerator. As analysis result, it had more dense structure due to the reaction product by adding material that used to enhanced strength. It had better resistance performance in chloride ion penetration, freezing–thawing and carbonation than shotcrete that used existing C12 A7 mineral-based accelerator.